Changes in Torque and Electromyography of Human Elbow Flexors fol-lowing Acute Eccentric Exercise - Mehdi Kargarfard; Anthony Shield (مجله دانشکده پزشکی اصفهان, 2012)
Background: Acute muscular exercise generally induces the development of fatigue that has detrimental effects on performance. The purpose of this study was to examine the effects of acute eccentric exercise (ECC) training on torque and electromyography (EMG) activity of human elbow flexors. Methods: Sixteen healthy male active subjects with no previous history of pathology of the elbow performed ten sets of 5 repetitions of maximal eccentric muscle actions training (ECC-T) with one arm using the calibrated electronically Biodex isokinetic dynamometer (System 3: Biodex) at 120° s-1 velocity of the dominant elbow flexors determined at the elbow joint of 90° (1.57 rad). Changes in maximal voluntary torque and EMG activity (root mean square (RMS)) of biceps brachii and brachialis muscles were measured after acute ECC. Findings: The acute ECC induced a significant torque reduction (P < 0.01). During the exercise session, mean maximal voluntary eccentric torque reduction reached 28.21 ± 10.20% (P < 0.001). Indeed, average maximal eccentric torque values dropped from 64.11 ± 11.28 N/m for the first three muscle actions of the first set to 46.05 ± 10.66 N/m for the final five muscle actions of the tenth set. Concurrent to the torque decrease, the RMS values of the biceps brachii and brachialis muscles at the same velocity were significantly lower after the exercise session (P < 0.05). After the acute exercise session, mean RMS values of the biceps brachii and brachialis muscles reduction reached respectively 15.16% and 13.87% (P < 0.001). Conclusion: These results showed that an acute ECC induced a significant voluntary maximal torque and EMG reduction of human elbow flexors during eccentric muscle actions.